Development of Au Promoted Pd/C Electrocatalysts for Methanol, Ethanol and Isopropanol Oxidation in Alkaline Medium - Su, Y.; Zhang, M.; Liu, X.; Li, Z.; Zhu, X.; Xu, C.; Jiang, San Ping (Electrochemical Science Group, 2012)
This research is aimed to investigate the Pt-free catalysts for alcohol electrooxidation in alkaline media. The results show that Pd is a good electrocatalyst for ethanol and isopropanol oxidation. The E-TEK Pt/C shows a much higher activity for methanol electrooxidation than Pd/C and PdAu/C electrocatalysts. The methanol shows a very bad activity of electrooxidation on the Pd/C and PdAu/C electrodes. Ethanol and isopropanol have higher oxidation activity on Pd/C than methanol in alkaline media. Gold can increase the palladium catalytic activity for methanol, ethanol and isopropanol oxidation. PdAu/C has higher catalytic activity and better steady-state electrolysis for ethanol and isopropanol oxidation than Pd/C and E-TEK Pt/C, however Au can’t enhance the stability and poisoning tolerance of Pd electrocatalysts for methanol oxidation.